Targets and moving goal posts: changes in waiting times in a UK emergency department. Issue 10 (27th September 2005) - Locker, T; Mason, S; Wardrope, J; Walters, S
Abstract : Objectives: To describe changes in the case mix, demographics, waiting times (WTs; time from arrival in the emergency department (ED) until seen by a clinician) and treatment times (TTs; time from seeing a clinician until leaving the ED) of adult patients presenting to the EDs in Sheffield, UK, between 1993 and 2003. Design: A retrospective analysis of routinely collected data. Results: Of a total of 252 156 patients included in the study, the proportion of attendees aged 16–29 years decreased from 38.7% in 1993 to 28.8% in 2003 (rate of change ( b )  =  −1.10% per year, 95% CI −1.20% to −0.82%, p<0.001) whereas the proportion aged 80–99 years increased from 6.2% to 10.4% ( b   = 0.37% per year, 95% CI 0.29% to 0.45%, p<0.001). The proportion of "minors" (patients not arriving by ambulance and subsequently discharged) fell from 71.1% in 1993 to 60.8% in 2003 ( b    =  −1.04% per year, 95% CI −1.36% to −0.73%, p<0.001). WTs increased from a median of 21 minutes in 1993 to 48 minutes in 2003 ( b    =  3.5 min per year, 95% CI 2.23 min to 4.77 min, p<0.001). The median TT for minors was unchanged but that for majors (patients arriving by ambulance and admitted to hospital from the ED) increased from 55 to 205 minutes ( b    =  11.55 min per year, 95% CI 6.54 min to 16.55 mins, p = 0.01). Conclusion: The demographics, case mix, and waiting times of patients presenting to EDs in Sheffield changed considerably over an 11 year period. There is evidence that the service for minor case patients improved slightly at the end of the period studied, but this is possibly at the expense of a deteriorating experience for major case patients.